Desempenho em pastagens e características de carcaça da 16a progênie dos rebanhos Nelore, Guzerá e Caracu de Sertãozinho (sp) - Razook, A. G.; de Figueiredo, L. A.; Ruggieri, A. C.; Nardon, R. F.; Cyrillo, JNDSG (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2002)
Forty one young bulls of herds selected for 378 day's weight (W378), born in 1996, were finished on pastures of Panicum Maximum (Jacq.), Panicum Maximum (Jaq) cv. Tanzania 1 and Brachiaria brizantha (Hoschst) Stapf cv. Marandu at the Sertaozinho Experimental Station, São Paulo State, Brazil. The samples, representing the W378 mean for each herd, were composed by 11 Nellore Selection (NeS) and by 10 of each one of the groups Nelore Control (NeC), Guzera Selection (GuS) and Caracu (Ca). The slaughter was carried out when the animals were 824 days older, with a body condition score averaging 7.6, in a 1-9 scale. The minimum and maximum adjusted means for the main traits, including all groups, were: average weight daily gain, 406 (NeC) and 501 g (NeS); slaughter weight (SW), 446.8 (NeC) and 544.3 kg (NeS); carcass weight (CW), 249.8 (NeC) and 309.7 kg (NeS); dressing percentage (DP), 54.0 (GuS) and 56.3% (NeC and NeS). In the 9(th) - 11(th) rib section: muscle, 59.6 (NeC) and 65.2% (Ca); fat, 15.6 (Ca) and 21.4% (NeC); bone, 18.9 (NeC) and 20.2% (GuS); fat thickness (FT), 2.0 (Ca) and 4.2 mm (NeC); loin eye area, 65.6 (NeC) and 71.1 cm(2) (NeS and Ca); Warner-Bratzler shear force (SF), 4.5 (Ca) and 6.6 kg (GuS) and total cooking losses (TCL), 22.5 (NeC) and 24.9% (GuS). The selection for weight promoted higher SW and CW in the NeS group, without changing the DP, the physical composition of the rib, SF and TCL in the meat. However, there was lower FT compared to NeC. The GuS animals had intermediates SW and CW, compared to NeS and Ca and lower DP. The Ca animals presented higher muscle percentage, in the rib section, and also higher meat tenderness compared to the meat of the Zebu animals.
Performance on pasture and carcass traits of the 16(th) selected progenies of Sertaozinho (SP-Brazil) Nelore, Guzera and Caracu herds
Keywords: body composition; daily gain; dressing percentage; meat tenderness; shear force